2020
DOI: 10.1080/13467581.2020.1798775
|View full text |Cite
|
Sign up to set email alerts
|

Performance of passive design strategies in hot and humid regions. Case study: Tangerang, Indonesia

Abstract: The building sector is one of the largest energy consumers worldwide. Especially in the hothumid Southeast Asian region, this sector consumes about 30% of primary energy demand. This is mainly dominated by air conditioning systems to provide space cooling and dehumidifying. In this paper, three passive design strategies to reduce cooling energy and attain a good daylight environment in an office in Tangerang, Indonesia, will be evaluated using both measurement and simulation methods. Improving thermal insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…While, adoption of PDS in Indonesia's construction industry can be traced back to a decade or earlier [29], in the last five years or so, there has been a surge in interest in PDS adoption among a wide range of construction stakeholders [30]. It was found that Indonesia was highly aware of PDS in the construction industry, however, the usage of the technology in the country was low [31]. Studies found very high awareness of PDS among the surveyed population of construction stakeholders, compared to the low adoption rate of only 4% [32,33].…”
Section: Pds Adoptionmentioning
confidence: 99%
“…While, adoption of PDS in Indonesia's construction industry can be traced back to a decade or earlier [29], in the last five years or so, there has been a surge in interest in PDS adoption among a wide range of construction stakeholders [30]. It was found that Indonesia was highly aware of PDS in the construction industry, however, the usage of the technology in the country was low [31]. Studies found very high awareness of PDS among the surveyed population of construction stakeholders, compared to the low adoption rate of only 4% [32,33].…”
Section: Pds Adoptionmentioning
confidence: 99%
“…Natural ventilation rooms are dependent on outdoor temperatures and the existence of openings allowing airflow between the rooms and adjacent environments [61]. Case A is suitable for ACB modification, since it gives the highest reduction in energy demand and is the closest to the comfortable temperatures, and the airtightness standard of 0.6 ACH [62,63] and the airflow standard of 0.35 m 3 /s [46] in Karachi. Figure 11 presents the heat transmission in the modified building envelope.…”
Section: Cases Energy Demand (Kwh)mentioning
confidence: 99%
“…Thus, it potentially can reduce the need for mechanical systems for cooling especially in tropical countries [27], [28]. Some of the passive design strategies that are most widely used in tropical countries, such as Indonesia, include responses to building and site orientation, applying shading or second skins, utilizing natural ventilation and natural light [29], [30]. This is due to more straightforward execution and relatively cheaper costs.…”
Section: Thermal and Visual Comfortmentioning
confidence: 99%